DRIVEN BY PASSION – NURAFIQAH - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, March 2017 – Having a passion for the martial arts has helped Nurafiqah Hamzah, a third-year student from Universiti Sains Malaysia (USM) to overcome her feelings of embarrassment and to join her Chinese friends in their practice of Shaolin Kung Fu. Nurafiqah 23, who hails from Kampung Pulau Igan in Mukah, Sarawak is the sole Malay Shaolin practitioner at USM.